Multivalvular Disease: Percutaneous Management in 2019 and Beyond - Magdalena Erlebach; Rüdiger Lange (Interventional Cardiology: Reviews, Research, Resources)
Patients with multivalvular disease (MVD) are common and often present with heterogeneous valve defects. Evaluation is complicated by interactions among various valve pathologies. Trials and guidelines focus primarily on single-valve disease, providing few recommendations for the treatment of patients with MVD. This article provides an insight into percutaneous treatment possibilities for this heterogeneous patient population.